An exploration into the value and use of English language pop songs for vocabulary acquisition in the Thai lower intermediate level EFL classroom: a guide for materials development. - Merton, Andrew (2016)
This study explored the attitudes and actions of 50 Thai teen and adult lower intermediate level English as a Foreign Language (EFL) students at a private language school in Bangkok towards using English language pop songs for vocabulary acquisition. The purpose of this was to better understand the educational value of the media in question, with the intention of developing a guide for materials design that could support teachers in the creation of their own related classroom activities and worksheets. This was achieved by using a questionnaire and follow-up focus groups that asked the students about general attitudes towards English language pop songs and how they might use them for learning new words. The questionnaire itself was designed with reference to an earlier study by Schmitt (1997), which had helped to inform the development of his taxonomy of vocabulary learning strategies (Ibid.). The materials design aspect of the present study was discussed with reference to a principled framework for pop song activity development that was adapted from the work of Tomlinson (2010) and Jolly & Bolitho (2011). The results section of this paper showed that the participants held an overall positive view of English language pop songs, and the media motivated them to learn encountered new words, including in a classroom context. The questionnaire also revealed some similarities between the vocabulary learning strategy preferences of those surveyed in this research and the Japanese students that took part in Schmitt’s (1997) investigation. The conclusion of this paper suggests that the present study offers a starting point for teachers in a similar educational context to conduct their own research on the topic. It also provides guidance for the development of classroom materials based on pop songs that encourage vocabulary learning, and ultimately, learner autonomy.